The relationship of Breaststroke Training on Knee Pain and Q Angle of Breaststroke and Crawl Swimmers - Sohrab Ghalehgir; Mehrdad Hefzollesan; Bahram Qarakhanlou Jamali; Asghar Tofighi (Wydawnictwo Naukowe Uniwersytetu Szczecińskiego, 2014)
Competitive swimmers have a high incidence of breaststroke-related knee injuries. The cause of the breaststroke swimmer’s knee, which is accompanied with medial pain of the knee joint, has not been clearly identified. The purpose of this investigation was to determine the biomechanical and anatomical factors which predispose subjects to injury. This study includes 60 breaststroke and crawl swimmers (16 ±3.2 years old) who have participated in 3–6-year-long swimming training in Tabriz city. The knee pain was evaluated with McGill’s pain questionnaire, and Q angle was measured with universal goniometry by knee radiography in standing position. The medial pain of knee joint increased significantly and the knee was only symptomatic when the swimmers performed the whip kick. Breaststroke swimmers were hardly able to complete training because of the knee pain. It is concluded that competitive training of breaststroke swimming for 6 months can cause exclusive injury and pain in swimmer’s knee. On the other hand, the result showed that there is a direct relationship between the swimmer’s Q angle amount and chance of the knee injury. This emphasizes a scrious consideration of Q angle states in breaststroke swimmers.